IDENTITY FORMATION IN CLANSMEN OF SARIKEI PAN-CHEN LAU’S CLAN ASSOCIATION - May, Lau Sii Min (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Clan association is an institution that bond people together with same surname, shared kinship, blood ties relationship, communicate with same language and believed that ancestors came from the same location. Sarikei Pan-Chen Lau’s Clan Association is one of the functioning clan associations in Sarikei. The core existence of Sarikei PanChen Lau’s Clan Association is to gather the Lau’s clan together as a family. Through the clan association, the Lau’s clan members can strengthen their cohesion and help them re-establish their self-esteem to guide their everyday lifestyle as a Chinese. The cultural collective identity formed a unique of the individual and group existence from the others. Human is cultural constructed. Thus, with the interaction of the local people, the clan members not only constructed their own identity as a Chinese, but they rather create their own living lifestyle and habits that is some different from Chinese culture. Therefore, this paper aims to find out the identity construction in Sarikei Pan-Chen Lau’s Clan Association among the clan member in creolization era.